Information security in ICT from an Islamic perspective - Ibrahim, Jamaludin; Ahmed Mohamed, Fatima; Abdulaziz, Nuha; Altaf Haqani, Alyami Effra (International Journal of Science and Research, 2014)
The primary objective of the study is to link, Islamic work ethics to computer use ethics. This paper will give intention and look at; to review the underlying concepts of ethics and Islamic ethics for computer usage. To find out some extremely related ethical issues of computer use such security and its clarification in point of Qur’an and Hadith. To suggest some ideas for managing these ethical issues in Islamic way. This paper seeks to analyze the nature of information as put onward using the Islamic worldview, and also study the concept of CIA (Confidentially, Integrity, Availability),this paper also give explanation on Evidentiary Rules: Integrity,Availability and Non Repudiation Measures.